1987
DOI: 10.1093/nar/15.7.2911
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hybridization kinetics of DNA attached to submkron latex particles

Abstract: We describe a novel method for attaching any DNA molecule to submicron latex beads and characterize the hybridization kinetic properties of these bead-DNA conjugates. The conjugates hybridize to DNA in solution with rates comparable to homogeneous hybridization reactions, are compatible with common hybridization conditions and are conveniently manipulated. They should thus serve as useful reagents for the fractionation and characterization of DNA and RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 10 publications
3
42
0
2
Order By: Relevance
“…New approaches to differential hybridization to identify rare mRNA clones from cDNA libraries using single-stranded cDNA (Boll etal., 1986); 5. Use of UV-irradiation to covalently bind DNA to solid supports (Stollar and Rashtchian, 1987) and immobilization of DNA to Sephacryl 500 dextran supports, which improve hybridization efficiencies to 80% compared to 20% with filter hybridization (Goldkorn and Prockop, 1986;Gingeras, Kwoh and Davis, 1987;Thompson and Gillespie, 1987;Wolf et al, 1987); 6. Hybridization strategies that reduce background from samples or enable the use of solution hybridization, which can reduce hybridization times to a few minutes (Gingeras, Kwoh and Davies, 1987;Karjalainen, Rouhainen and Soderlund, 1987;Nicholls, Langdale and Malcolm, 1987;Wilkins and Snell, 1987;Palva, Nyberg and Palva, 1988;Urdea etal., 1988); 7.…”
Section: Nucleic Acid Hybridization Methodsmentioning
confidence: 99%
“…New approaches to differential hybridization to identify rare mRNA clones from cDNA libraries using single-stranded cDNA (Boll etal., 1986); 5. Use of UV-irradiation to covalently bind DNA to solid supports (Stollar and Rashtchian, 1987) and immobilization of DNA to Sephacryl 500 dextran supports, which improve hybridization efficiencies to 80% compared to 20% with filter hybridization (Goldkorn and Prockop, 1986;Gingeras, Kwoh and Davis, 1987;Thompson and Gillespie, 1987;Wolf et al, 1987); 6. Hybridization strategies that reduce background from samples or enable the use of solution hybridization, which can reduce hybridization times to a few minutes (Gingeras, Kwoh and Davies, 1987;Karjalainen, Rouhainen and Soderlund, 1987;Nicholls, Langdale and Malcolm, 1987;Wilkins and Snell, 1987;Palva, Nyberg and Palva, 1988;Urdea etal., 1988); 7.…”
Section: Nucleic Acid Hybridization Methodsmentioning
confidence: 99%
“…NucleoLink strips were selected for the present study because the binding efficiency of DNA to NucleoLink has been shown to be five to 10 times higher than to CovaLink (Oroskar et al, 1996). NucleoLink strips are made of an activated heat-stable polymer and support covalent binding of DNA by carbodiimide-mediated condensation, and these strips can be assembled in micro-well format and used in micro-well plate readers (Chu et al, 1983 ;Ghosh & Musso, 1987 ;Oroskar et al, 1996 ;Rasmussen et al, 1991 ;Wolf et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Wolf et al compared rates for hybridization of a radiolabeled oligomer to DNA-coated particles with solution-phase hybridization rates and demonstrated that rates on particles approached those in solution (ϳ0.2x-1x) for the conditions tested (33). Later Jungell-Nortamo and co-workers determined that capture of radiolabeled nucleic acid hybrids onto plasmid-coated microparticles, although somewhat slower than solution-phase hybridization, was significantly faster than capture onto membrane-immobilized plasmid (34).…”
mentioning
confidence: 99%